BEHAVIOUR OF TORSIONAL-DOMINANT DUAL-SISTEM REINFORCED CONCRETE WITH FRICTION PENDULUM BEARING BASE ISOLATION UNDER MASSIVE EARTHQUAKE LOAD - Wijaya Putra, Ardhi
Now a days, Base Isolation System has been used widely in practice because of the awareness and needs that damage in some structures during an earthquake is not allowed. Furthermore, all of the non-structural components of the structure which is falling apart during an earthquake can cause casualties. Base isolation system is a system that isolate or seperate the upper-structure and the lower-structure. Base isolation system can also be said as a soft story mechanism which is planned to be happened in the isolation system level. Base isolation has a principle to increase the structure period in order to reduce the earthquake acceleration induce to the structure. Besides, the implementation of the isolation system makes most of the earthquake energy is absorbed by it There are many kind of base isolation system, but what the writer is going to discuss is the sliding type or what is known as Friction Pendulum Bearing. FPS is an isolation system which has the recentering capability. FPS movement is similar to a simple pendulum in which it moves along the circular. FPS disipate the earthquake energy through the friction between the articulated slider and the concave sliding surface. The objectives of this study is to compare two torsion-dominant structures which one is conventional fixed base structure and the other one is the isolated structure. The analysis which is going to be used is both response spectrum analysis and non-linear time history analysis. Parameters which are going to be compared are period, base shear, roof absolute acceleration, roof drift ratio, interstory drift, and the number of hinge.